Critical Secularism: Perfectionism and Anti-perfectionism - Mohammad Shojaeian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Liberals claim that they do not impose any restrictions on the critique of ideas and institutions because any restriction means restricting freedom of expression as one of the most important aspects of freedom. Accordingly, in liberal discourse, insults to divine prophets are defended as an example of freedom of expression. The central theme of the book “Is Criticism Secular?” is related to the above discussion. This book contains articles written by  Talal al-Assad and Saba Mahmoud and criticizes the liberal view of criticism and its relation to freedom of expression. This article examines and criticizes these views. Both Assad and Saba Mahmoud tried to reject the “dual rational argument” that puts Christianity, secularism, rationality, tolerance, and freedom on one side, and Islam, fundamentalism, obedience, bigotry, and limitation on the other side. Assad emphasizes the violation cases that exist in the functioning and existing laws of modern societies. However, he should have taken a critical analytical approach to the perfectionism inherent in the views of Western thinkers, especially in liberal discourse, as a violation of the moral neutrality they claim. Saba Mahmoud rejects the claim of separation of religion from politics by emphasizing modern discourse and underlines the bias of the Western critical tradition. His discussion complements the issues that Talal al-Assad seeks.